Analisis Alih Kode dan Campur Kode serta elemen Visual pada Iklan Make-Up PT. Paragon di Instagram - Aziza, Sonya Nur; Dallyono, Ruswan (Faculty of Languages and Arts, Universitas Negeri Padang, 2024)
This qualitative study analysed the use of code-switching and code-mixing in makeup advertisements from four brands of PT Paragon Technology and Innovation (Emina, MakeOver, InstaPerfect, and Wardah) on Instagram, employing Barthes' (1988). Semiotic method was used to explore denotative and connotative meanings in the ads. Denotation refers to the literal meaning of signs, while connotation reveals additional meanings influenced by culture and ideology. The findings indicate that code-switching and code-mixing are used to capture audience attention and create a modern brand image. For instance, MakeOver advertisements use English language to convey an international impression, whereas Emina employs code-mixing to make messages more dynamic and relevant to bilingual audiences. Practical implications of this research include assisting companies in developing effective marketing strategies and crafting engaging and grammatically appropriate ad content. Moreover, the study is expected to enhance consumer critical thinking towards advertisements and aid policymakers in establishing language usage guidelines in advertising. Overall, this research demonstrates that makeup advertisements not only promote products but also shape consumer identities and self-images, reflecting global trends and socio-cultural dynamics.